INFORMATION SYSTEM DESIGN FOR FINAL PROJECT CONSULTATION - Hirawati Oemar; Sumarto Sumarto; Aan Komariah; Maulana Malik Ibrahim; Anis Saleh (Center for Study and Journal Management FTI UMI, 2021)
This Final Project is one of the graduation requirements for Industrial Engineering students at the Islamic University of Bandung. Currently.Â The final project consultation process is conducted manually using physical documents owned by each student as proof of consultation in the form of a consultation card. The problem faced was the difficulty in monitoring consultations and recording consultation discussions which were not well organized. The purpose of this study is to design a consulting information system using the prototyping method. The prototyping method is a system development method used to describe the system. The stages in this method consist of: (1) The planning stage is the identification of system requests. (2) the analysis phase analyzes the existing business processes in the final project section and identifies functional and non-functional requirements, (3) the design phase includes the interaction design of systems, processes, data and logical systems and physical interfaces. (4) Implementation phase of database and website development using PHP language and MySQL database. The results obtained from this study are business process consulting for the Final Project after the implementation of the proposed information system; final project consulting information system design which is expected to facilitate the consultation process in terms of time and consultation file documentation